Evaluating Potential Crop Water Requirement (Case Study: Islamic Azad University, Science and Research Branch of Tehran) - Maedeh Bidabadi; Hossein Babazadeh; Mahdi Sarai Tabrizi (محیط زیست و مهندسی آب, 2019)
Urban green space has always faced challenges to estimate the actual water requirement of plants due to the diversity of different plant species, their dispersal, and the different densities. In this research, we have tried to estimate the need for the University of Science and Research Branch with an area of 10.59 hectares. First, it has been necessary to identify and categorize existing species and finally 77 plant species were identified on the site of Science and Research Branch. In addition, due to the diversity in trees and green spaces, the California Journal’s method was used to calculate crop coefficient. The meteorological data required from the meteorological stations in Tehran was then obtained by the Iran Meteorological Organization and processed by the CROPWAT program. In the next step, the potential evapotranspiration was calculated using Penman Monteith method. Finally, the water requirement for green space was determined by the California University method. The results of this study indicate that the maximum water requirement is 246033.7 cubic meters in July. Also, in January, February, November, and December, due to the long-term average rainfall, this amount provides the water requirement of the site and there is no need for irrigation during this period.